Dynamics identification and control of an industrial robot - Jamisola, Rodrigo S., Jr. (Animo Repository, 1999)
It is known that the performance of a robot can be improved with the incorporation of robot dynamics into its controller. However, derivation and implementation of a complete robot dynamic model is not widely used in practice mainly because of the difficulty in modelling dynamic behavior and the lack of information about the parameters that describe such behavior, especially link inertias. Furthermore, most industrial robots do not allow modification of their control algorithms, with only a few allowing the Proportional and Derivative (PD) gains of their controllers to be altered, that further hampers robot full dynamics control implementation. In this paper, we present a method to identify the lumped inertial parameters together with an estimate of viscous friction, and the derivation and implementation of a full dynamics model of an industrial robot. We provide details of the method, discuss implementation issues and show experimental results on the 7-DOF Mitsubishi PA-10 robot.